Age‐related ultrastructural changes of the basement membrane in the mouse blood‐brain barrier. Issue 2 (19th November 2018) - Ceafalan, Laura Cristina; Fertig, Tudor Emanuel; Gheorghe, Teodora Cristina; Hinescu, Mihail Eugen; Popescu, Bogdan Ovidiu; Pahnke, Jens; Gherghiceanu, Mihaela
Abstract: The blood‐brain barrier (BBB) is essential for a functional neurovascular unit. Most studies focused on the cells forming the BBB, but very few studied the basement membrane (BM) of brain capillaries in ageing. We used transmission electron microscopy and electron tomography to investigate the BM of the BBB in ageing C57BL/6J mice. The thickness of the BM of the BBB from 24‐month‐old mice was double as compared with that of 6‐month‐old mice (107 nm vs 56 nm). The aged BBB showed lipid droplets gathering within the BM which further increased its thickness (up to 572 nm) and altered its structure. The lipids appeared to accumulate toward the glial side of the BM. Electron tomography showed that the lipid‐rich BM regions are located in small pockets formed by the end‐feet of astrocytes. These findings suggest an imbalance of the lipid metabolism and that may precede the structural alteration of the BM. These alterations may favour the accretion of abnormal proteins that lead to neurodegeneration in ageing. These findings warrant further investigation of the BM of brain capillaries and of adjoining cells as potential targets for future therapies.